Thermal depoling of high Curie point Aurivillius phase ferroelectric ceramics - Haixue Yan; Hongtao Zhang; Michael J. Reece; Xianlin Dong (2005)
Thermal depoling of high Curie point Aurivillius phase ferroelectric ceramics